Implementation of Agroforestry Program Learning in the Framework of Sustainable Environmental Management - Yogi Orlando; Lisdawati Wahjudin (Global Education Journal, 2026)
Governmental Studies is a branch of social science that studies the implementation of state power in regulating, managing, and serving the public. This study aims to analyze the effectiveness of the agroforestry program implemented by the Kuningan Regency Forestry Service Branch VIII in supporting sustainable environmental management and to identify obstacles and potential tenurial conflicts during the transition period of the Special Management Forest Area (KHDPK) policy. The method used is descriptive qualitative with a case study approach. The results indicate that the agroforestry program is relatively effective in balancing ecological and economic functions through the integration of forestry and agricultural crops. However, its implementation still faces obstacles such as limited extension workers, low capacity of Forest Farmer Groups (KTH), and legal uncertainty following the transfer of management from Perum Perhutani. The program's sustainability depends on strengthening local institutions and optimizing Non-Timber Forest Products (NTFPs).